2012
DOI: 10.1371/journal.pone.0032638
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Sub-Saharan Africa: Cross-Sectional Surveys in Four Rural and Urban Communities

Abstract: BackgroundCardiovascular disease (CVD) is the leading cause of adult mortality in low-income countries but data on the prevalence of cardiovascular risk factors such as hypertension are scarce, especially in sub-Saharan Africa (SSA). This study aims to assess the prevalence of hypertension and determinants of blood pressure in four SSA populations in rural Nigeria and Kenya, and urban Namibia and Tanzania.Methods and FindingsWe performed four cross-sectional household surveys in Kwara State, Nigeria; Nandi dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

59
302
11
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 332 publications
(374 citation statements)
references
References 54 publications
59
302
11
2
Order By: Relevance
“…Other studies in Africa which have included individuals aged 15 years and above, have shown similar increases in the prevalence of hypertension across the age groups [6,25]. Our results show that age is associated with hypertension, with the prevalence rising to 30% in those aged 65 years or more, which agrees with other studies [2,26,27]. A few studies in Africa have explored hypertension by gender with one showing no difference after adjusting for age [28].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Other studies in Africa which have included individuals aged 15 years and above, have shown similar increases in the prevalence of hypertension across the age groups [6,25]. Our results show that age is associated with hypertension, with the prevalence rising to 30% in those aged 65 years or more, which agrees with other studies [2,26,27]. A few studies in Africa have explored hypertension by gender with one showing no difference after adjusting for age [28].…”
Section: Discussionsupporting
confidence: 92%
“…The association between overweight, obesity, large waist circumference and hypertension was found in both males and females in our study. It is estimated that a 10 kg increase in body weight raises blood pressure by 3 mmHg systolic and 2.3mmHg diastolic blood pressure [16], and this association concurs with many other studies in Africa [2,26,27,29]. Increased blood sugar was also associated with raised blood pressure, which also concurs with other studies worldwide [14].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…6 In Kenya, hypertension treatment and control rates have been reported at 9 % and 3 %, respectively. 7 Poor linkage to hypertension care, manifested as delays in seeking care after screening and referral, has been shown to be associated with increased mortality among pregnant women in sub-Saharan Africa. 8 Thus, screening and early linkage to hypertension care are critical components of hypertension management.…”
Section: Introductionmentioning
confidence: 99%